2017
DOI: 10.1177/0269215517698834
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of constraint-induced movement therapy compared with bimanual intensive training in children with unilateral cerebral palsy: a systematic review

Abstract: It is not possible to conclude whether constraint-induced movement therapy or bimanual intensive training is more effective than the other in children with unilateral cerebral palsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 50 publications
1
16
0
1
Order By: Relevance
“…CIMT for children with CP, was the only intervention comprehensively and empirically compared to other intervention options, using head‐to‐head RCT comparisons identified in our search strategy. CIMT was: (i) compared head‐to‐head with Bimanual Training showing no difference between the approaches (Sakzewski et al ., ; Tervahauta, Girolami & Øberg, ); and (ii) combined with Bimanual Training and/or Botulinum toxin A, showing no additive benefits occurred from a combined intervention approach (Hoare et al ., ). These researcher's concluded ‘intensity’ of practice was the key ingredient of these effective CP approaches (Sakzewski et al .; Tervahauta et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…CIMT for children with CP, was the only intervention comprehensively and empirically compared to other intervention options, using head‐to‐head RCT comparisons identified in our search strategy. CIMT was: (i) compared head‐to‐head with Bimanual Training showing no difference between the approaches (Sakzewski et al ., ; Tervahauta, Girolami & Øberg, ); and (ii) combined with Bimanual Training and/or Botulinum toxin A, showing no additive benefits occurred from a combined intervention approach (Hoare et al ., ). These researcher's concluded ‘intensity’ of practice was the key ingredient of these effective CP approaches (Sakzewski et al .; Tervahauta et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…However, in the Hybrid-CIMT programme, strength needs to be sufficient in order to be able to grasp and hold in the first part of the programme where CIMT is performed, and the hand is trained unimanually. 45 The dosage of mCIMT and BIT differs among the articles found in the literature 33 , 44 48 ; evidence shows that BIT and mCIMT have similar effects when the same dose is compared in children with moderate bimanual functional performance. 33 , 48 , 49 In the study of Deppe et al , applied in children with unilateral cerebral palsy or other non-progressive hemiplegia (aged 3.3–11.4 years), 45 two intensive protocols were performed with a total dose of 80 h: hybrid-CIMT protocol comprised of 60 h of CIMT and 20 h of BIT in a clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“… 45 The dosage of mCIMT and BIT differs among the articles found in the literature 33 , 44 48 ; evidence shows that BIT and mCIMT have similar effects when the same dose is compared in children with moderate bimanual functional performance. 33 , 48 , 49 In the study of Deppe et al , applied in children with unilateral cerebral palsy or other non-progressive hemiplegia (aged 3.3–11.4 years), 45 two intensive protocols were performed with a total dose of 80 h: hybrid-CIMT protocol comprised of 60 h of CIMT and 20 h of BIT in a clinical setting. The results of this study suggested higher treatment gains for more severely impaired children with hybrid-CIMT.…”
Section: Introductionmentioning
confidence: 99%
“…To improve manual abilities in the CP population, different approaches include treatments that attempt to reduce hand impairment by increasing hand dexterity and strength (Moon et al, 2017) and others that emphasize hand function with movement constraint or promoting bimanual activities (Tervahauta et al, 2017). According to the International Classification of Functioning Disability and Health, rehabilitation professionals should attend to both body and activity domains.…”
Section: Introductionmentioning
confidence: 99%